2021
DOI: 10.1007/s11481-021-10028-1
|View full text |Cite
|
Sign up to set email alerts
|

Eugenol, a Component of Holy Basil (Tulsi) and Common Spice Clove, Inhibits the Interaction Between SARS-CoV-2 Spike S1 and ACE2 to Induce Therapeutic Responses

Abstract: Spike S1 of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) binds to angiotensin-converting enzyme 2 (ACE2) on host cells to enter the cell and initiate COVID-19. Since ACE2 is a favorable enzyme, we were interested in finding a molecule capable of binding spike S1, but not ACE2, and inhibiting the interaction between spike S1 and ACE2. Holy basil (Tulsi) has a long history as a medicine for different human disorders. Therefore, we screened different components of Tulsi leaf and found that eugenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 45 publications
2
35
0
Order By: Relevance
“…In silico and thermal shift assays reported that the eugenol is associated with spike S1, but it did not have any impact on ACE2. Consequently, eugenol strongly suppressed the entry of pseudo typed SARS-COV-2 and decreased SARS-COV-2 spike S1-induced activation of NF-κB and in the human A549 lung cells, the expression of IL-6, IL-1β, and TNFα was also found to be reduced, confirming its potential for selective targeting of spike S1 of SARS-COV-2 ( Paidi et al, 2021 ).…”
Section: Antiviral and Immunomodulatory Mechanisms Of Recommended Bio...mentioning
confidence: 84%
See 1 more Smart Citation
“…In silico and thermal shift assays reported that the eugenol is associated with spike S1, but it did not have any impact on ACE2. Consequently, eugenol strongly suppressed the entry of pseudo typed SARS-COV-2 and decreased SARS-COV-2 spike S1-induced activation of NF-κB and in the human A549 lung cells, the expression of IL-6, IL-1β, and TNFα was also found to be reduced, confirming its potential for selective targeting of spike S1 of SARS-COV-2 ( Paidi et al, 2021 ).…”
Section: Antiviral and Immunomodulatory Mechanisms Of Recommended Bio...mentioning
confidence: 84%
“…Further, similar dosing of tulsi has shown a potent antiviral effect by avoiding the entry of the virus into the cell. In other research, Paidi et al (2021) screened the various component of the tulsi leaf. By the Alpha Screen assay, it was observed that the eugenol significantly inhibited the interaction between spike S1 and ACE2.…”
Section: Antiviral and Immunomodulatory Mechanisms Of Recommended Bio...mentioning
confidence: 99%
“… 23 , 33 The mechanism by which carnation may reduce the severe form of COVID-19 involves interference of SARS-CoV-2 S1-protein binding to the angiotensin-converting enzyme 2 (ACE2) receptor. 34 Moreover, carnation has been shown to increase the availability of oxygen by improving blood supply to both the heart and the brain. 35 Carnation has also been reported to be beneficial for the management of chronic coughs, shortness of breath, and maintaining a normal heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption to binding between ACE2 and spike S1 could be therapeutically beneficial. Based on their ongoing studies, Dr. Pahan’s lab, explored and identified Eugenol, a component of holy basil (Tulsi), capable of binding spike S1, but not ACE2, and inhibiting the interaction between spike S1 and ACE2 (Paidi et al 2021 ). Using an AlphaScreen-based assay, only Eugenol, but not other major components of Tulsi leaf, was found to block the interaction between spike S1 and ACE2.…”
Section: Original Researchmentioning
confidence: 99%
“…Next comes the issue’s review paper, “Racial Health Disparity and COVID-19” (Kumar et al 2021b ) followed by three original research articles. One of these primary research papers examines a potential treatment approach using the herbal product, “Eugenol, a component of holy basil (Tulsi) and common spice clove, and reporting that this herbal product inhibits the interaction between SARS-CoV-2 spike S1 and ACE2 to induce therapeutic responses” (Paidi et al 2021 ). The next paper describes original meta-analysis research, “Network meta-analysis on the changes of amyloid precursor protein expression following SARS-CoV-2 infection” (Camacho et al 2021 ).…”
mentioning
confidence: 99%